Describing Emotiveness Via Expressive Means and Stylistic Devices in English Short Stories (“The Luncheon” By W. S. Maugham, “In Another Country” By Ernest Hemingway, “The Cherry Tree” By Alfred Coppard) (Journal of Pedagogical Inventions and Practices, 2022)
In this article, some short stories characterized by the category of stylistic devices are considered by stylistic analyses. Futhermore, the article consists of pieces taken from different English literary texts. As regards stylistic devices are hold peculiar features of fictional texts. Stylistic devices can always provide emotionality on any particular texts.